2016
DOI: 10.18632/oncotarget.10261
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 down-regulates the immunosuppressive capacity of olfactory ecto-mesenchymal stem cells in murine collagen-induced arthritis

Abstract: Olfactory ecto-mesenchymal stem cells (OE-MSCs) are a population of cells which has been recognized as a new resident stem cell type in the olfactory lamina propria. OE-MSCs have been shown to exert their immunosuppressive capacity by modulating T cell responses, including up-regulation of regulatory T cells (Tregs) and down-regulation of Th1/Th17 cells. As an inflammatory cytokine, IL-17 plays a critical role in orchestrating the inflammatory response during the development of collagen-induced arthritis (CIA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…These stimulations might differentially affect the properties of lymphocytes, making them more or less susceptible to MSCs than the physiological pathway activated by anti-CD3/CD28 + IL-2 stimulation. Finally, the use of MSCs derived from the olfactory cells of mice, in contrast to the use of human BM-derived MSCs by us and Sivanathan, might account for the different result observed by Tian [22]. When analyzing cotreatments with inflammatory cytokines, in accordance with our results, Han [21] found IFNy to be sufficient to induce immunosuppression by MSCs and IL-17 to not synergize with IFNy for immunosuppression induction.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These stimulations might differentially affect the properties of lymphocytes, making them more or less susceptible to MSCs than the physiological pathway activated by anti-CD3/CD28 + IL-2 stimulation. Finally, the use of MSCs derived from the olfactory cells of mice, in contrast to the use of human BM-derived MSCs by us and Sivanathan, might account for the different result observed by Tian [22]. When analyzing cotreatments with inflammatory cytokines, in accordance with our results, Han [21] found IFNy to be sufficient to induce immunosuppression by MSCs and IL-17 to not synergize with IFNy for immunosuppression induction.…”
Section: Discussionsupporting
confidence: 83%
“…The role of IL-17 in MSCs immunobiology has been the subject of a few studies [21][22][23][24]. By using different in vitro migration assays, Krstić observed that IL-17 induced migration and invasion in MSCs [24]; however, neither correlations with the immunomodulatory properties of MSCs nor combinations of different inflammatory cytokines were analyzed.…”
Section: Discussionmentioning
confidence: 99%
“…IL17 alone or together with IFNγ and TNFα on MSCs has been shown to have a positive effect on their immunosuppressive functions since IL17A addition considerably enhances their immunosuppressive potential ( 33 , 34 ). However, it has been shown that IL17 could also reduce the suppressive capacity of OE-MSCs, mainly by downregulating their production of immunosuppressive factors including NO 2 , IL10, TGF-β1, as well as PD-L1 ( 35 ). In the present study, we demonstrate that the IL17/IL17RA axis plays a key role on MSCs immunomodulatory properties since the inhibition of IL17A receptor significantly impairs the capacity of MSCs to inhibit the proliferation and generation of proinflammatory Th17 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistent effects have also been described for IL17-stimulated MSCs. Indeed, IL17 has also been described to reduce the immunosuppressive capacity of olfactory ecto-mesenchymal stem cells (OE-MSCs), mainly by downregulating the levels of inhibitory factors produced by OE-MSCs, such as NO, IL10, TGF-β, as well as PD-L1 ( 35 ). Thus, the exact role of IL17 regarding the immunosuppressive effect of MSCs remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, IL-17 treatment inhibited the capacity of OE-MSCs in generating Treg cells as well as their capacity to suppress the generation of Th1 and Th17 in vitro and in vivo using the CIA model. Furthermore, knockdown of IL-17R in OE-MSCs significantly enhanced their therapeutic effect in reducing CIA progression [121]. Although the studies compared MSCs from different sources known to display some discrepancies in their functions [26], further investigations are required to better understand the effect of IL-17 on MSC immunomodulatory capacity (Figure 1).…”
Section: Mscs Preconditioning To Improve Their Therapeutic Featurementioning
confidence: 99%